Enhancement of electricity production in microbial fuel cells using a biosurfactant-producing co-culture (2023)
Microbial fuel cells are bio-electrochemical devices that enable the conversion of chemical energy into bioelectricity. In this manuscript, the use of biosurfactants (Tween 80 and surfactin) and the effect of coculturing E. coli and L. plantarum were used to investigate the generation of bioelectricity coming from an H-type microbial fuel cell. In this setup, E. coli acts as an electron donor while L. plantarum acts as an in situ biosurfactant producer. It was observed that the use of exogenous surfactants enhanced electricity production compared to conventional E. coli cultures. The utilization of Tween 80 and surfactin increased the power generation from 204 µW m−2 to 506 µW m−2 and 577 µW m−2, respectively. Furthermore, co-culturing E. coli and L. plantarum also resulted in a higher power output compared to pure cultures (132.8% more when compared to using E. coli alone and 68.1% more when compared to using L. plantarum alone). Due to the presence of surfactants, the internal resistance of the cell was reduced. The experimental evidence collected here clearly indicates that the production of endogenous surfactants, as well as the addition of exogenous surfactants, will enhance MFC electricity production.